2022
DOI: 10.3389/fmicb.2022.838808
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Induces Microglia Gasdermin D-Dependent Pyroptosis Through Activating the NLR Family Pyrin Domain Containing 3 Inflammasome

Abstract: Herpes simplex virus type 1 (HSV-1) is a highly prevalent virus in humans and causes severe forms of inflammation, such as herpes simplex encephalitis (HSE). Pyroptosis is a new inflammatory cell death triggered by inflammasome and cysteine-requiring aspartate protease-1 (caspase-1) activation. Nonetheless, HSV-1 induces encephalitis, and cell death mechanisms are not understood. In this study, we confirmed for the first time that the DNA virus HSV-1 triggers Gasdermin D-dependent pyroptosis by activating NLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…This leads to the production of mature IL-1β, an inflammatory cytokine, and activation and release of caspase-1 resulting in host cell death. This reveals that inflammasome activation and GSDMD-dependent pyroptosis are important mechanisms of HSV-1-induced pathogenesis and inflammation [118].…”
Section: Dna Viruses Mediated Pyroptosismentioning
confidence: 89%
See 1 more Smart Citation
“…This leads to the production of mature IL-1β, an inflammatory cytokine, and activation and release of caspase-1 resulting in host cell death. This reveals that inflammasome activation and GSDMD-dependent pyroptosis are important mechanisms of HSV-1-induced pathogenesis and inflammation [118].…”
Section: Dna Viruses Mediated Pyroptosismentioning
confidence: 89%
“…However, it causes severe inflammation called herpes simplex encephalitis (HSE) [117]. A recent study by Hu et al reported that HSV-1 induces GSDMD pyroptosis by activation of NLRP3 inflammasomes, which induces the production of IL-1β expression and caspase-1 release in mouse microglia [118]. Karaba et al observed that HSV-1 is capable of activation of the non-canonical inflammasome without NLRP3, ASC, and caspase-1, which results in the activation of IL-1β but not IL-18 in pr-inflammatory human THP-1 macrophages [119].…”
Section: Dna Viruses Mediated Pyroptosismentioning
confidence: 99%
“…Furthermore, this study investigated the mechanism of HK1‐regulated periapical inflammation. Previous studies indicated that HK1‐dependent glycolysis regulates activation of the NLRP3 signalling pathway (Moon et al, 2015), which can directly activate the protease caspase‐1 to induce gasdermin D‐dependent pyroptosis and facilitate the release of IL‐1β (Huang et al, 2021; Hu et al, 2022). Moreover, the NLRP3 signalling pathway has been shown to sense metabolites such as palmitate, uric acid and cholesterol crystals and is inhibited by ketone bodies during metabolic flux (Hughes & O'Neill, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, disulfiram, which is clinically utilized to treat alcoholism, inhibits GSDMD activation and shields mice in the lethal LPS-induced sepsis model [ 106 ]. It is worth noting that GSDMD is also a key element of pyroptosis, and many authors have acknowledged the potential role of pyroptotic pathway during an HSV-1 infection [ 107 , 108 , 109 , 110 ]. Furthermore, there is also a cell-intrinsic program that modifies the neutrophil proteome in the circulation and causes the progressive loss of granule content and reduction of the NET-forming capacity [ 111 ].…”
Section: Diagnosis and Therapeuticsmentioning
confidence: 99%